GEOMETRIC CONSTRUCTION OF THE TREE-DIMENSIONAL FINITE ELEMENTS OF THE SERENDIP FAMILY - Manoilenko, О.С. (Journal of Information Technologies in Education (ITE), 2012)
The traditional approach to the basal functions construction in the finite element method reduces to the solution of linear algebraic equations system relative to the parameters assigned the interpolar polynome, and to the further trial function estimation. This approach conjugates with the certain calculating difficulties and demands big expenditures of machine time. The new geometric approach to the basal functions construction is developed which gives the possibility to obtain the new alternative models. The geometric modeling methods of the tree-dimensional finite elements of the serendip family on the cube are shown in the work.